Энциклопедия Амосова. Раздумья о здоровье - Амосов Николай Михайлович (АСТ, 2005)
Экземпляры: ф.16 (2005) / Инвентарный номер: 49251 / Цена: / Сис.шифр: 51.204.0 / Авт.знак: А 62 / ГРНТИ: 76 / ББК: 51.204.0